Produção de saber no contexto da EDISCA – Escola de Dança e Desenvolvimento Humano: tecendo uma pedagogia da expressividade - Araújo, Carlos Gilano Andrade do (2018)
The research intends to investigate the production of knowledge in the context of EDISCA – School of Dance and Human Development, aiming to weave elements for a Pedagogy of expressiveness. Theoretically, it is referred to the Pradier´s (2009) and Bião´s ethnocenology (2003), Katz´s (2005) and Grainer´s (2006) concept of Corpomídia, Barba´s Theatrical Anthropology (1994) and Burnier´s studies about actor-dancer's expressive body sensitization (2009); also, in Freire´s thought (1968), and his Pedagogy of Autonomy. Analyzing the phenomena of the production of knowledge, in EDISCA, we will dialogue with the educational reflection built in dance, in this institution, laying the foundations for a Pedagogy of Expressiveness. The research, is mediated by visual ethnography (GUADITANO, 1999) and educational biographies (DELORY-MOMBERGER, 2008), which involves the artistic-pedagogical processes of creation and presentation of Dance performances – through EDISCA´s art and education praxis. Observing the knowledge raised by the experience of its artists, teachers-choreographers and students-dancers, we have found elements of a pedagogy of expressiveness, concluding that it will be of great importance the development of aesthetic intelligence concept. Seen as the amalgam of artistic, political and ethics, as well as highlighting the value of the articulation between art and life, in their everyday existentiality, in the context of the educative works that deal with children and young people from communities on the margins of social rights. Specifically, it is considered that collective processes experienced in Dance point to the learning and expression of knowledge through the senses of the body, involving in a tessitura of the diverse ontological dimensions.